A study of dynamic information display and decision-making in abstract trust games. Issue 113 (May 2018) - Schaffer, James; O'Donovan, John; Marusich, Laura; Yu, Michael; Gonzalez, Cleotilde; Höllerer, Tobias
Highlights: Dynamic user interfaces can influence human cooperative behavior in trust games. UI and information availability were manipulated in a user study of the Diner's Dilemma. Overall, user cooperation and situation awareness increased with information availability. Users were more likely to retaliate against defection than they were to initiate defection. A user interface has different effects on human behavior based on co-actor exploitation. Abstract: User interfaces that display dynamic information have the ability to influence decision makers in networked settings where many individuals collaborate. To understand how varying levels of information support affects behavior (cooperation vs. defection) in a social dilemma, a user interface (UI) was developed and an online experiment ( N =901) was conducted based on the iterated Diner's Dilemma, a version of the n-player Prisoner's Dilemma. There were 3 main findings: (1) as more UI support was given, participants became more likely to retaliate against defection than they were to initiate defection; (2) participant situation awareness (SA) increased as more UI support was given but decreased in the presence of forgiving co-actors; and (3) the need for UI support to make good decisions was diminished as co-actors became more likely to exploit. These results can inform the design of information support tools for collaborative settings.